Determinants of Halal-Labeled MSME Food Purchase Decisions among Muslim Generation Z Consumers - Nadira Amalia; Irni Rahmayani Johan (Journal of Child, Family, and Consumer Studies, 2026)
Despite Indonesia’s large Muslim population and the rapid development of its Islamic economic ecosystem, the limited availability of halal-certified packaged food products produced by MSMEs remains a challenge in meeting the needs of Muslim consumers. This study aimed to examine the effects of religiosity, subjective norms, and halal awareness on purchase decisions regarding halal-labeled packaged food products produced by MSMEs. This cross-sectional study involved 191 Muslim Generation Z consumers in Greater Jakarta who had purchased packaged MSME food products within the previous three months. Respondents were recruited using voluntary sampling and data were collected through an online questionnaire administered via Google Forms. The data were analyzed using descriptive statistics in IBM SPSS Statistics version 25.0 and Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that religiosity and subjective have significant positive effects on purchase decisions regarding halal-labeled MSME food products, whereas halal awareness does not significantly influence purchase decisions. Among the examined, religiosity emerged as the strongest determinant of purchase decisions. These findings suggest that efforts to promote the consumption of halal-labeled products should focus on strengthening consumers' religious understanding to support purchase decisions regarding halal products